The Reality of Music Arts Learning at Citra Cemara Elementary School - Gouwtama, Rama Gouwtama; Haerani, Reni (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to describe the reality of music art learning at Citra Cemara Elementary School. The problem is focused on the independent curriculum used in schools in music art learning in phases A, B, and C. The focus of the problem in phase A is the difficult transition and the development of different students. The focus of the problem in phase B is the problem faced by independent learning skills. The focus of the problem in phase C is the use of technology. The Independent Curriculum Theory is used to overcome these problems. This curriculum emphasizes student-centered learning, flexibility in content and methods, and character and competency development. Data were collected through interviews, observations, and documentation and analyzed qualitatively. In-depth interviews with music art teachers to obtain information about experiences, views, and perceptions related to music art learning at Citra Cemara Elementary School. Direct observation in class during music art learning at each phase. Documentation is carried out to see teaching materials, results, and evaluations in the music art learning process in writing. This study concludes that with the implementation of the independent curriculum, students in each phase have achieved quite good learning outcomes on average. However, there are still some things that can be improved, such as information on teacher training, which is expected to be communicated to schools, especially in music arts teacher training.